A community for students. Sign up today!
Here's the question you clicked on:
 0 viewing

This Question is Closed

inkyvoyd
 one year ago
Best ResponseYou've already chosen the best response.1d/dx f(g(x))=f'(g(x))g'(x)

andrea408
 one year ago
Best ResponseYou've already chosen the best response.0f(θ) = y f'(θ) = dy/dθ u = sec(θ) du/dθ = sec(θ)tan(θ) y = u² dy/du = 2u Then, f'(θ) = 2usec(θ)tan(θ) ==> 2(sec²(θ))sec(θ)tan(θ) ==> 2sec³(θ)tan(θ) I hope this helps!

inkyvoyd
 one year ago
Best ResponseYou've already chosen the best response.1f(x)=x^2 g(th)=sec th

kausarsalley
 one year ago
Best ResponseYou've already chosen the best response.0dw:1362873411456:dw dw:1362873506755:dw

dangbeau
 one year ago
Best ResponseYou've already chosen the best response.0so the answer is the same as me f'(θ)= \[2\sec ^{2}\theta \tan \theta\], right? but i don't know why the right answer is \[2\theta \sec \theta ^{2} \tan \theta ^{2}\] can anyone explain it?

inkyvoyd
 one year ago
Best ResponseYou've already chosen the best response.1the answer is the one that you got and others gave. http://www.wolframalpha.com/input/?i=d%2Fdx+sec^2+x the answer 2th sec^2 th tan^2 th is incorrect.

dangbeau
 one year ago
Best ResponseYou've already chosen the best response.0hm... i have another answer \[\sec ^{2} \theta=\sec \theta ^{2}\] it's equal, right?

inkyvoyd
 one year ago
Best ResponseYou've already chosen the best response.1no, of course not. sec^2(th)= sec th*sec th sec(th^2)=sec(th*th)

NoelGreco
 one year ago
Best ResponseYou've already chosen the best response.0No, it's not correct.Rewrite sec^2 x as (sec x)^2, then power and chain rules.

dangbeau
 one year ago
Best ResponseYou've already chosen the best response.0wait, this one http://www.wolframalpha.com/input/?i=d%2Fdx+sec^2+x you solve it as f(x)=sec^2x, but i ask f(x)=secx^2 o.0

dangbeau
 one year ago
Best ResponseYou've already chosen the best response.0how to get that answer?

inkyvoyd
 one year ago
Best ResponseYou've already chosen the best response.1use f(x)=sec x g(x)=x^2 then f'(g(x))g'(x)=tan(x^2)sec(x^2)*d/dx x^2=2x tan(x^2)sec(x^2)

inkyvoyd
 one year ago
Best ResponseYou've already chosen the best response.1does that make sense?

inkyvoyd
 one year ago
Best ResponseYou've already chosen the best response.1okay  so the chain rule makes more sense to you now?

dangbeau
 one year ago
Best ResponseYou've already chosen the best response.0yup, thanks sooo much ^^
Ask your own question
Ask a QuestionFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.